Раціоналізація системи збуту молока на регіональному ринку - Краснодєд, Тетяна Леонідівна; Краснодед, Татьяна Леонидовна; Krasnodied, Tetiana (My University, 2015)
UK: В статті досліджено канали реалізації молока в Запорізькій області та розраховано ефективність функціонування кожного каналу збуту. Водночас визначено об'єктивну необхідність раціоналізації структури каналів збуту на ринку молока в регіоні за рахунок пошуку найкрупніших покупців та впровадження нових маркетингових збутових концепцій, спрямованих на європейський ринок. EN: In the article the substantiation about what conditions in the market orientation of the production of each plant advisable as intensively expand its range of consumer commodity products, especially if there is a fairly significant proportion konkurentozaminnykiv the market. This certainly applies to dairy producers. Reach new market segments, customers gain primarily involves opening new sales channels and adoption of its position on the old, proven point of sale, the survival of these producers rivals by delivering competitive products. The right choice in terms of sales and channel forming rational structure of milk or any milk range of products allow manufacturers to increase profitability and provide stability process in the profit and agricultural processing plants. Studied the channels of milk in the Zaporozhye region and calculated the efficiency of each distribution channel. At the same time set the objective need for rationalization of the structure of distribution channels on the milk market in the region by finding the largest customers and introducing new marketing concepts marketing aimed at the European market. Statistically proven that in the long term to increase sales of milk processing organizations will improve the return on sales in the region as a whole, and the formation of an effective channel structure of milk should be given the financial results from the sale of milk for each channel and the use of external marketing orientation of companies.
Keywords: молоко; молокопродукти; переробні підприємства; канали реалізації; регіональний ринок; рентабельність продаж; товарна продукція; мilk; dairy products; processing plants; distribution channels; regional market; return on sales; commodity products